Pterygosoma (Pterygosoma) pseudotrapelus sp. nov. (Acariformes: Pterygosomatidae)—ectoparasite of Pseudotrapelus sinaitus (Squamata: Agamidae) from Jordan - Bochkov, Andre V.; Melnikov, Daniel A.; Melnikov, Roman. A. (Zootaxa, 2009)
A new ectoparasitic mite species, Pterygosoma (Pterygosoma) pseudotrapelus sp. nov. (Acariformes: Pterygosomatidae) is described from Pseudotrapelus sinaitus (Squamata: Agamidae) collected from Jordan. According to leg setation, this species belongs to group 4 established by Jack (1964). It differs from the other three species of the group by the following female characters: from P. sinaita Jack by the presence of 15–18 pairs of long peripheral setae (vs. 3–4 pairs of short setae in P. sinaita), and 1 pair of strong and stout genital setae (vs. 3 short spur-like setae); from P. foliosetis Jack by the long peripheral setae with slightly expanded tips (vs. strongly expanded setae in P. foliosetis), barbed filiform anterior-lateral setae (vs. smooth expanded setae), and pseudoanal setae being much longer than wide (vs. as long as wide setae); from P. rhipidostichata Bertrand et al. by the presence of 23–28 pairs of antero-lateral setae (vs. over 50 pairs in P. rhipidostichata), peripheral setae slightly expanded apically (vs. pointed setae), presence of a pair of the stout genital setae (vs. lacking genital setae), and the presence of 4 pairs of pseudoanal setae of uniform shape (vs. 5 pairs of setae of different shape).